Entrepreneurial Development of C Pengembangan Wirausaha Cabai Rawit Varietas Bara F-1 Pada Kelompok Tani Wanita Berdikari Melalui Aplikasi Teknologi ULiBiCo, EM4 dan Plastikultur-MPHP : Entrepreneurial Development of Cayenne Pepper Variety Bara F-1 in the Berdikari Women Farmers Group through Technology Applications ULiBiCo, EM4 and MPHP - Sakul, Ernest Hanny; Manoppo, Jacklin Stella Salome; Ngangi, Jantje; Rayer, Debby Jacqueline Jochebed; Nangoy, Wiesye Maya Selfia; Lawalata, Helen Joan; Rompas, Christny Ferdina Evie; Djarang, Rievo Handry; Sakul, Zefanya Escriva Rafael; Tengker, Anita Costanci Christine; Rawung, Stanny Sicilia; Silangen, Patricia Mardiana; Rumondor, Desire Atna Sridanty (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
Tonsealama is a village that has the potential to develop an environmentally friendly organic-based agribusiness farmer group business that has maximum agribusiness products and high economic value. The livelihood of the villagers is dominated by farmers and farm laborers and only a small part is engaged in services. The development of agribusiness entrepreneurship of raw chilli bara F1 variety for women's farmer groups in Keroit village is deemed necessary to be developed, in order to utilize idle land and organic household waste products. This is also a business opportunity to increase household economic income and the welfare of women's farmer groups and their members. Based on the above, the Community Partnership Program for Women Farmers Group in Tonsealama Village was implemented. This program includes the use of agricultural technology products in the form of ULiBiCo (Unima Liquid Biofertilizer Combination) and Effective Microorganism (EM4) applications that help the decomposition process of chicken manure waste into quality organic fertilizer, and combined with the use of silver black plastic mulch technology (MPHP) and bioinsecticide-based pest control, it turns out to be able to provide good yields in the cultivation of cayenne pepper plants of the bara F-1 variety. The morphological character of the first harvest obtained is the quality of the cayenne pepper fruit, which has a sharp fruit, with a length of ± 3 cm, a diameter of ± 0.4 cm, shiny red skin, spicy taste, and can be harvested at the age of 78 - 100 days after planting (HST), the average yield of this cayenne pepper is 0.85 - 1.0 kg per plant, with a weight per fruit ranging from 0.9 - 1.8 grams and has a potential yield of 8.9 - 10 tons / ha. ABSTRAK Tonsealama merupakan desa yang memiliki potensi untuk dikembangkannya sebuah usaha kelompok tani agribisnis berbasis organik ramah lingkungan yang memiliki produk hasil agribisnis yang maksimal dan bernilai ekonomi tinggi. Mata pencaharian penduduk desa masih didominasi oleh para petani. Pengembangan wirausaha agribisnis cabai rawit varietas bara F1 pada kelompok tani wanita di desa Tonsealama dirasa perlu untuk dikembangkan, guna memanfaatkan lahan tidur dan produk limbah organik rumah tangga. Hal ini juga merupakan sebuah peluang usaha untuk meningkatkan pendapatan ekonomi rumah tangga dan kesejahteraan kelompok tani wanita beserta anggotanya. Berdasarkan hal tersebut di atas, maka dilaksanakanlah Program Kemitraan Masyarakat Kelompok Tani Wanita di Desa Tonsealama. Program ini meliputi pemanfaatan produk teknologi pertanian berupa aplikasi ULiBiCo (Unima Liquid Biofertilizer Combination) dan Effective Microorganism (EM4) yang membantu proses dekomposisi limbah kotoran ayam menjadi pupuk organik berkualitas, dan dikombinasikan dengan pemanfaatan teknologi mulsa plastik hitam perak (MPHP) serta pengendalian hama berbasis bioinsektisida, ternyata mampu memberikan hasil panen yang baik dalam budidaya tanaman cabai rawit varietas bara F-1. Karakter morfologi hasil panen pertama yang diperoleh yaitu kualitas buah cabai rawit memiliki buah lancip, dengan panjang ± 3 cm, diameter ± 0,4 cm, kulit buah berwarna merah mengkilap, berasa pedas,  dan dapat dipanen pada umur 78 - 100 hari setelah tanam (HST), rata-rata hasil cabai rawit ini yaitu 0,85 - 1,0 kg per tanaman, dengan bobot per buah berkisar 0,9 – 1,8 gram dan memiliki potensi hasil 8,9 – 10 ton/ha.